KEWENANGAN BADAN BANK TANAH DALAM PEROLEHAN TANAH TERLANTAR DALAM MENJAMIN KETERSEDIAAN TANAH UNTUK KEPENTINGAN UMUM - Christo, Nathanael Mario; Harriestha Martana, Putu Ade (Kertha Semaya : Journal Ilmu Hukum; Vol 11 No 5 (2023)DO - 10.24843/KS.2023.v11.i05.p14, 2023)
Penelitian ini bermaksud untuk mengetahui kewenangan bank tanah (Land Bank) dalam perolehan tanah terlantar dalam menjamin ketersediaan tanah untuk kepentingan umum. Dewasa ini, penelataran tanah masih marak terjadi hal ini sungguh menganggu cita cita dari negara Indonesia itu sendiri. Jika kita melihat berdasarkan         pembukaan konstitusi UUD 1945 , dengan seiringnya Penelataran tanah yang marak terjadi sungguh menganggu kepentingan umum sekitar, hal ini disebabkan karena tanah tersebut tidak dipertanggungjawabkan oleh pemegang haknya. Metode penelitian yang digunakan di dalam penelitian ini ialah Penelitian Normatif atau dikenal dengan Studi Kepustakaan, hal ini untuk meneliti kekaburan mengenai pengaturan mengenai Bank tanah dalam memperoleh tanah terlantar dalam menjamin kepentingan umum. Di dalam penelitian ini penulis bertujuan untuk mengetahui apakah badan bank tanah ini dapat mengelola tanah yang terlantar dengan memenuhi asas kepentingan umum yang terdapat pada UU No 5 Tahun 1960 Tentang Pe r aturan Dasar Pokok-pokok Agraria. Jika kita melihat dari segi eksistensinya badan bank tanah mempunyai tugas sebagai eksekutor dalam mengelola tanah sehingga diharapkan bank tanah dapat menjalani tugasnya dengan baik . This study aims to knowing the authority of the land bank agency in the acquisition of abandoned land in ensuring the interest Nowadays, neglect of land is still rife, this really disturbs the ideals in Indonesian state itself. If we are based on the preamble to the constitution of the 1945 Constitution, that the ideals of the Indonesian people are to prove the Indonesian nation and all the spilled waters of Indonesia and to promote public welfare, educate the nation's life and implement a world based on independence, eternal peace and social justice. The widespread neglect of land really disturbs the surrounding public interest, this is because the land is not designated by the right holder. The impact of neglect of land is very disturbing to people in Indonesia, for example, empty land is used as a garbage disposal. This is very disturbing community activities, the need for policies that must be issued by the government. This policy is implemented with the creation of an independent or special institution (Sui Generis), namely the land bank agency. Land Bank Agency is the agency as the executor in managing the land. In this study the author will discuss whether this land bank agency can manage abandoned land by fulfilling the public interest contained in. seeing from the basis of Article 3 paragraph (1) PP no. 64 of 2021 concerning the Land Bank ing Agency has the functions of planning, land acquisition, land management,    land use and land distribution. If we look at the function of the bank agency, it has the task of being an executor in managing land, so it is hoped that the land bank can carry out its duties properly .